Implementing placental-growth-factor (PLGF) measurements in suspected pre-eclampsia—-Challenges in clinical practice. (November 2021) - Wojcik, Maria; Karouni, Faris; Jindal, Sucheta; Kapaya, Habiba
Abstract: Objectives: As a part of NHS' Innovation and Technology Payment programme (ITP), pregnant women were offered Placental Growth Factor (PLGF)-based testing to help rule out pre-eclampsia (PET) – a serious condition that affects approximately 2.3% of the female population. The study was aimed to evaluate the implementation of PLGF-based testing at United Lincolnshire Trust Hospitals (ULHT). Study Design: The soluble FMS like Tyrosine kinase 1/placental growth factor (sFlt-1/PLGF) ratio test was launched at ULHT on 8th October 2020. The project involved a review of an electronic maternity database (MEDWAY) for all women who had sFLT-1/PLGF ratio test performed at ULHT over a 5-month period (October 2020-February 2021). The sFlt-1/PLGF ratio was recorded alongside clinical outcome. Women were classified as low, moderate, and high risk for development of PET if the sFlt-1/PLGF ratio was ≤ 38, 39–84 and ≥ 85 respectively. Reasons for admission were further investigated and adherence to the sFLT-1/PLGF protocol was monitored to evaluate staff performance. Data was then statistically analysed with χ2 and T-test for categorical and continuous variables respectively. Finally, sensitivity and specificity of the sFLT-1/PLGF was assessed with an ROC curve. Results: A total of 236 women had sFlt-1/PLGF ratio test performed in a five-month period. A two-time point analysis (a "during implementation" and "post implementation phase") showed a significant decrease in the admission rates in the post-implementation phase in low-risk group (28.5% during implementation vs 11.3% post-implementation, P < 0.05). Further analysis showed greater staff adherence to the sFLT-1/PLGF protocol in the post-implementation period. The high-risk group demonstrated shorter time from test to delivery, earlier gestational age at delivery and lower birth weight (P < 0.05). Conclusions: The study outcomes resulted in a successful submission of a business case. Successful triage of low-risk women at the point where historically admissions were considered reduced clinical workload and enabled better utilisation of resources by allowing focussed care on high-risk women for an optimal maternal and perinatal outcome.